“If We Must Die”: Writing the African American Double Battle in WWI - Botelho, Teresa (Cadernos de Literatura Comparada (teste), 2014)
Not Only War: The Story of Two Great Conflicts, the only WWI African American novel written by a veteran remained a forgotten and neglected text for a long time. Contemporary critics either ignored it or found it lacking as good fiction. But its recent re-edition in 2010 has brought it to the attention of new generations of readers and critics, filling a gap in a space that had hitherto been exclusively represented by the post-war literary renditions of the experience of the returning soldier. This article discusses its import in the context of African American combat literature as both fiction and a memoir that stands as a reminder of the cycle of promise and disappointment that turned the war experience into a powerful catalyst for both the literary and artistic articulations of the Harlem Renaissance and the early civil rights movement.